2024
DOI: 10.1007/s40617-024-00918-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurodiversity-Affirming Applied Behavior Analysis

Lauren Lestremau Allen,
Leanna S. Mellon,
Noor Syed
et al.

Abstract: Individuals within the Autistic and Neurodivergent communities have shared numerous concerns about applied behavior analysis (ABA). These criticisms often relate to the ableism reflected within current practices, which have impeded the dignity and autonomy of many individuals with disabilities served through ABA. Both within the field and outside of the field, there is a growing acknowledgment of the need to listen, reflect, and reconsider approaches to service delivery, which can ultimately benefit service re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 161 publications
0
6
0
Order By: Relevance
“…Autistic individuals possess unique insights into their own lives and communities. Therefore, the efficacy of ABA might be more influenced by individual variances rather than gender differences [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autistic individuals possess unique insights into their own lives and communities. Therefore, the efficacy of ABA might be more influenced by individual variances rather than gender differences [33].…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, research has consistently shown a higher prevalence of ASD diagnoses in males than in females. This could potentially introduce a bias in the research data, with more males being represented in ABA studies than females [3,33]. Some studies have discovered that female individuals with ASD exhibited significantly better social interaction and social communication skills compared to male individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autistic individuals have unparalleled expertise in their own lives and their communities. Thus, the effectiveness of ABA could be influenced more by individual differences rather than gender differences [31,32]. Autism is a spectrum disorder with a wide range of symptoms and severity that can vary greatly among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, research has consistently reported a higher rate of ASD diagnoses in males than in females. This could potentially lead to a bias in the research data, with more males being represented in ABA studies than females [29,31]. Some studies have found that female individuals with ASD had significantly better social interaction and social communication skills compared to male individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%